Defining CDK12 as a tumor suppressor and therapeutic target in mouse models of tubo-ovarian high-grade serous carcinoma - Jean Ching-Yi Tien; Yali Zhai; Rong Wu; Yuping Zhang; Yu Chang; Yunhui Cheng; Abigail J. Todd; Christina E. Wheeler; Shuqin Li; Rahul Mannan; Caleb Cheng; Brian Magnuson; et al. (Proceedings of the National Academy of Sciences, 2025)
Ovarian cancer is the sixth leading cause of cancer death among American women, with most fatalities attributable to tubo-ovarian high-grade serous carcinoma (HGSC). This malignancy usually develops resistance to conventional chemotherapy, underscoring the need for robust preclinical models to guide the development of novel therapies. Here, we introduce an HGSC mouse model generated via Ovgp1 -driven Cre recombinase effecting CRISPR/Cas9-mediated deletion of Trp53, Rb1 , and Nf1 tumor suppressors in mouse oviductal epithelium ( m-sgPRN model). Cyclin-dependent kinase 12 (CDK12) inactivation—frequently observed in human HGSC—is associated with poorer outcomes, DNA damage accumulation (including tandem duplications), and increased tumor immunogenicity. In our system, coablation of Cdk12 ( m-sgPRN;Cdk12KO ) recapitulated hallmark features of HGSC, while accelerating tumor progression and reducing survival. In a conventional (Cre-lox-mediated) Trp53/Nf1/Rb1 triple knockout model with concurrent Cdk12 ablation ( PRN ; Cdk12KO mice), we observed T cell–rich immune infiltrates mirroring those seen clinically. We established both models as subcutaneous or intraperitoneal syngeneic allografts of CDK12 -inactivated HGSC that exhibited sensitivity to immune checkpoint blockade. Furthermore, a CRISPR/Cas9 synthetic lethality screen in PRN;Cdk12KO -derived cell lines identified CDK13—an essential paralog of CDK12—as the most depleted candidate, confirming a previously reported synthetic lethal interaction. Pharmacologic CDK13/12 degradation (employing YJ1206) demonstrated enhanced efficacy in cell lines derived from both m-sgPRN;Cdk12KO and PRN ; Cdk12KO models. Our results define CDK12 as a key tumor suppressor in tubo-ovarian HGSC and highlight CDK13 targeting as a promising therapeutic approach in CDK12 -inactive disease. Additionally, we have established valuable in vivo resources to facilitate further investigation and drug development in this challenging malignancy.